The murder sorority eaudiobook - Karp, Marshall (NYPD Red, 2022)
Finding a single assassin in a city of nine million is daunting.Finding five is a nightmare. Join the NYPD Red team in their most explosive case ever. The series from James Patterson and Marshall Karp has always been a must-read. But Karp's latest, NYPD Red 7: The Murder Sorority, tops them all, making it a must-read-now! Lower Manhattan: A sniper's bullet ends the life of a high-profile New Yorker. Five miles uptown, a second prominent victim has his throat slashed. And that's only the beginning. A network of professional assassins is on the loose in New York City. Trained by the US military, they're on their own now, with a new unit called Kappa Omega Delta. Killers On Demand. NYPD Red detectives Kylie MacDonald and Zach Jordan are called in to hunt them down, but these mercenaries are as gifted in the art of escape as they are in snuffing out lives. It's the biggest professional challenge the Red team has ever faced, and before it's over, both Kylie's and Zach's personal lives will change. Forever.